Adatom bond-induced geometric and electronic properties of passivated armchair graphene nanoribbons. Issue 25 (7th July 2015) - Lin, Yu-Tsung; Chung, Hsien-Ching; Yang, Po-Hua; Lin, Shih-Yang; Lin, Ming-Fa
<x xml:space="preserve">Abstract</x> The geometric and electronic properties of passivated armchair graphene nanoribbons, enriched by strong chemical bonding between edge-carbons and various adatoms, are investigated by first-principle calculations.